2020
DOI: 10.3390/molecules25112471
|View full text |Cite
|
Sign up to set email alerts
|

Collective Locomotion of Human Cells, Wound Healing and Their Control by Extracts and Isolated Compounds from Marine Invertebrates

Abstract: The collective migration of cells is a complex integrated process that represents a common theme joining morphogenesis, tissue regeneration, and tumor biology. It is known that a remarkable amount of secondary metabolites produced by aquatic invertebrates displays active pharmacological properties against a variety of diseases. The aim of this review is to pick up selected studies that report the extraction and identification of crude extracts or isolated compounds that exert a modulatory effect on collective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 208 publications
(239 reference statements)
0
19
0
Order By: Relevance
“…Collagen has been shown to increase keratinocyte proliferation, positively acting on cell entry in the mitotic phase (Luparello et al, 2020). Thus, collagen synthesis and deposition into the wound is essential during wound healing (Han et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Collagen has been shown to increase keratinocyte proliferation, positively acting on cell entry in the mitotic phase (Luparello et al, 2020). Thus, collagen synthesis and deposition into the wound is essential during wound healing (Han et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, to cite just a few examples, anticancer compounds have been found among the primary and secondary metabolites of starfishes and Mediterranean ascidians [20,21], and extracts or isolated molecules obtained from marine invertebrates have been proven to exert a modulatory effect on collective cell migration, a process at the basis of different biological events such as neoplastic cell metastasization and wound repair [22]. Chemicals with histone deacetylase inhibitory properties, whose wide range of potential biomedical applications is generally acknowledged, have also been extracted and identified in preparations from marine invertebrates [23].…”
Section: The Marine Animal Species As a Source Of Bioactive Moleculesmentioning
confidence: 99%
“…They show a relatively smooth surface with several pores and can be found as encrusting species growing over coral rubbles [29]. In 2013, Yamazaki et al [30] reported the cytotoxic activity of the pentacyclic alkaloid papuamine (1S,2E,4E,6S,7R,12S,14R,20R,22S,27R)-15,19diazapentacyclo[18.7.0.0 6,14 .0 7,12 .0 22,27 ]heptacosa-2,4-diene, Figure 1), the major constituent of these sponges, in MCF-7 breast cancer cells.…”
Section: Autophagy Modulators From Poriferamentioning
confidence: 99%
See 1 more Smart Citation
“…These products contribute to the adaptation mechanisms to the specific life conditions in the greatly different marine ecosystems [26]. A large proportion of invertebrate-derived extracts and isolated compounds has shown active pharmacological properties, such as anticancer, antimicrobial, and anti-inflammatory, among others, with an extensive spectrum of biomedical applications that makes them already approved or prospective drugs of marine origin with promising results for different therapeutic purposes [27][28][29][30][31][32]. Within this scenario, the aim of this review is to gather selected studies that reported the extraction and identification of marine invertebrate-derived chemicals that possess HDACi properties and recapitulate the molecular, biochemical, and/or physiological aspects, where available, which are associated with the examined molecules.…”
Section: A Brief Insight Into Histone Deacetylases and Histone Deacetylase Inhibitorsmentioning
confidence: 99%